2016
DOI: 10.1089/jwh.2015.5462
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antenatal Partner Support on Pregnancy Outcomes

Abstract: Background: While there has been considerable attention given to the multitude of maternal factors that contribute to perinatal conditions and poor birth outcomes, few studies have aimed to understand the impact of fathers or partners. We examined associations of antenatal partner support with psychological variables, smoking behavior, and pregnancy outcomes in two socioeconomically distinct prebirth cohorts. Materials and Methods: Data were from 1764 women recruited from an urban-suburban group practice (Proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 35 publications
9
77
0
11
Order By: Relevance
“…shown that low levels of partner support are associated with higher levels of antenatal anxiety and depression during pregnancy (Cheng et al, 2016) and that low levels of shared communication, relationship satisfaction and emotional and instrumental support increase the risk of developing depression (Pilkington, Milne, Cairns, Lewis, & Whelan, 2015). Women with cancer who were in an unsupportive relationship with their partners had higher risk of developing anxiety symptoms, manifested lower levels of positive affect and had lower levels of reported quality of life (Borstelmann et al, 2015;Gustavsson-Lilius, Julkunen, & Hietanen, 2007;Kaliampos & Roussi, 2018).…”
Section: Ta B L E 5 Extracts For the Theme 'Partner Role'mentioning
confidence: 99%
“…shown that low levels of partner support are associated with higher levels of antenatal anxiety and depression during pregnancy (Cheng et al, 2016) and that low levels of shared communication, relationship satisfaction and emotional and instrumental support increase the risk of developing depression (Pilkington, Milne, Cairns, Lewis, & Whelan, 2015). Women with cancer who were in an unsupportive relationship with their partners had higher risk of developing anxiety symptoms, manifested lower levels of positive affect and had lower levels of reported quality of life (Borstelmann et al, 2015;Gustavsson-Lilius, Julkunen, & Hietanen, 2007;Kaliampos & Roussi, 2018).…”
Section: Ta B L E 5 Extracts For the Theme 'Partner Role'mentioning
confidence: 99%
“…Also, Owili et al [27] found a reduction in the proportion of women obtaining ANC services with increasing age in Kenya. On the contrary, studies from Navaneetham and Dharmalingam (2002); Klemetti et al [28]; Cheng et al [29], and Uppadhaya et al [30] confirm that older women were more likely to use antenatal care services than their younger counterparts. The reason may be due to the fact that older women might have gathered immense knowledge on the need of antenatal care services, which may positively influence their use of ANC services.…”
Section: Related Literaturementioning
confidence: 99%
“…When assessing perinatal distress, possible protective and impeding factors must be evaluated. For example, in some studies, perinatal distress correlated with weak social support (16,17) and dissatisfaction in the partner relationship (17,18). Being married (19) is reportedly a protective factor for perinatal distress.…”
Section: Introductionmentioning
confidence: 99%